Risk Analysis of Wheat Yield Losses at the County Level in Mainland China - Li, Xuan; Fang, Shibo; Zhu, Yongchao; Wu, Dong (Frontiers in Environmental Science, 2021)
There have been few researches focused on quantifying wheat yield loss risk based on high-resolution long-term historical data. What’s more, the existence of area scale effect reduces the certainty and spatial comparability of results. In this study, a long-term wheat yield and planting area data at county level from 1981 to 2010 was used. The spatial distribution of wheat yield loss risks was analyzed in the mainland of the People’s Republic of China (China for short). An improved comprehensive risk index of yield loss risk was established by integrating the reduction rate, coefficient of variation, and the probability of occurrence for different yield reduction rate after removing the effect of area scale. 874 main wheat-growing counties in mainland of China were divided into lowest, lower, moderate, higher, and highest risk areas based on it. The high-risk areas are located in Yellow-Huai-Hai Plain, including Shandong, Henan, northern Anhui and parts of Jiangsu Province.